NILAI ETIKA LINGKUNGAN DALAM ANTOLOGI CERPEN KEKASIH YANG TAKUT CACING KARYA RENI ERINA DKK SERTA RELEVANSINYA TERHADAP PEMBELAJARAN SASTRA - sari, anita (Universitas Negeri Surabaya, 2023)
This research is motivated by the lack of public awareness of environmental issues, resulting in a lot of damage to the earth. This is based on early character cultivation for environmental love that has not been cultivated in society. This study aims to describe the value of environmental ethics in the anthology of short stories of Lovers who are Afraid of Worms initiated by Reni Erina. The approach used in this research is qualitative approach. This research uses analytical descriptive method. The theory used is the theory of environmental ethics. The data collection technique is through listening and recording techniques, by reading carefully the short story and recording quotations with natural elements. The result of the research shows that there are environmental ethics values in the twelve short stories in the anthology, namely respect for nature, responsibility for nature, solidarity with nature, love and care for nature, living simply and in harmony with nature, no harm, democratic, and fair to nature. The value of environmental ethics in this research can be relevant to Indonesian language learning as a form of character education.